INFECTION BY HELMINTHS IN MYLOSSOMA DURIVENTRE CUVIER, 1817, A CHARACID FROM THE CENTRAL AMAZON, BRAZIL - Farias da Silva, Elizângela (2012)
This study describes the parasitic fauna of Mylossoma duriventre caught at Lake Coari, a tributary of the middle Solimões River, in the state of Amazonas (central Amazon, Brazil) and the relative condition factor (Kn). Out of 70 necropsied specimens, 90% had the gills parasitized by the helminth Anacanthorus paraspathulatus Kritsky, Boeger & Van Every, 1992 (Dactylogyridae: Anacanthorinae) and the intestine by Eustrongylides Jägerskiöld 1909 (Nematoda: Dioctophymatidae) larvae. Atotal of 19,763 specimens of A. paraspathulatus were collected, but the infection by Eustrongylides sp. larvae seemed to be accidental, only three hosts were trophically infected. However, there was no significant difference (p<0.05) in the Kn of parasitized and nonparasitized fish, indicating that the intensity these parasites has not affected the health of the host. This is the first report of parasitic infection rates for M. duriventre, as well of infections by Eustrongylides sp. for this host.